Effects of locally produced microbial phytase on humoral immunity and blood characteristics in broilers vaccinated against Newcastle and Infectious Bursal Diseases - Islam, Rakibul (2014)
In a phosphorus (P) deficient animal diet, phytase supplementation improves the bioavailabilities of P as well as other nutrients by phytate hydrolysis and indirectly, plays a role in biological function of many metabolic processes. In consequence, hypothetically, chicken health in terms of immune responses associated with hematological parameters, blood biochemical constituents and live body weight might be influenced. Phytase production commercially,focuses only on the soil fungus Aspergillus, but many possible sources of microbial novel phytases remain unexplored. In Malaysia, around 30 strains of potential phytase producing soil bacteria were successfully harvested and they show good enzymatic activities and characteristics favouring physiology of chicken gut. In addition, some bacterial phytases, especially those of the genera Bacillus and Enterobacter, exhibits a pH optimum ranging from 6.0 to 8.0, close to the physiological pH of the stomach of chicken. Newcastle disease (ND) and infectious bursal disease (IBD) are the most important diseases for poultry worldwide, which can cause huge economic losses in the poultry industry. In Malaysia, therefore, the possibility of using the locally produced bacterial phytase from Enterobacter sakazakii ASUA273 in broilers fed low P diet (0.19%) and vaccinated against ND and IBD could be justified. The objective of the study was to determine the effects of microbial phytases on humoral immunity and blood characteristics in association with the live body weights of broilers vaccinated with ND and IBD vaccines. Five experiments (Experiment l, ll, lll, IV and V) were carried out. The first three trials (Experiment l, ll and lll) were carried out in broilers fed low P diet with four doses (0 FTU/kg-1, 500 FTU/kg-1, 1000 FTU/kg-1, and 1500 FTU/kg-1 of diet) of local bacterial phytase grouped as T0 (control), T1, T2, and T3, accordingly on ND, IBD, and both of ND and IBD vaccinations, respectively. In each trial, 180 day-old-male broilers were allocated to four treatment groups with 12 cages comprising three replicates, each cage containing 15 birds. The last two trials (Experiment lV and V) were conducted with broiler chickens fed the same diet, with two doses (0 FTU/kg-1 and 1500 FTU/kg-1 of diet) of Natuphos® grouped as T0 (control) and T1, accordingly on ND and IBD vaccinations, respectively. Ninety (92) day-old-male broilers per trial were randomly assigned into two treatments, each contained three replicates of 15 chicks each. They were maintained on formulated experimental basal diet based on available phosphorus (0.19%), lasted up to six weeks of age with feed, and water made attainable for ad libitum consumption. Birds received two doses of ND vaccines (ND ‘V4 HR’) at day-old and 21 day-old,respectively and one dose of IBD vaccine (IBD UPM93) at 10 day-old. Two birds were randomly selected weekly, from each treated group (8 and 4 birds per replicate were selected from experiments using local phytase and Natuphos® supplementation, respectively) and live body weights were measured. These birds were then slaughtered for blood collection to prepare serum for quantification of antibody (Ab) titers, IgM, and IgG and jejunal fluid were collected to quantify IgA throughout the experiment. At the end of experiment, blood was furthermore collected for determining the complete hemogram and blood biochemistry. Antibody titers (ND and IBD), IgM, IgG, and IgA were detected by ELISA using commercial kits. Although a hematology analyzer using commercial reagents measured the complete hemogram, other parameters (differential leukocyte count (DLC), packed cell volume (PCV), icterus index, and total plasma protein) were determined manually. All blood biochemical constituents were determined with the help of a chemistry analyzer. Data of humoral immunity with live body weights,and blood characteristics were analyzed based on factorial arrangement (treatments × weeks) of completely randomized design (CRD) and CRD,respectively. Results of humoral immunity of vaccinated broilers showed that serum Ab titers (ND and IBD), IgM, and IgG contents did not increase by phytase supplementation in low P diet. However, mucosal secretory IgA concentrations of vaccinated birds increased consistently and significantly (P<0.05) with increasing phytase doses throughout the experiments. Results of live body weights of broilers showed that body weights were linearly and significantly (P<0.05) increased to graded levels of phytase supplementation at weekly intervals. Cumulative effects of mucosal IgA contents and live body weights of broilers also showed the significant interaction between effects of phytase levels and effects of weeks. Overall, phytase dose at 1500 FTU/kg-1 of diet and over the age of 6 weeks showed the best performance. On the overall, findings on complete hemogram and blood biochemical constituents did not show any consistent and significant (P<0.05) difference that would suggest that phytase supplementation in corn-soybean based P deficient diet affected the health of broilers. It was therefore, concluded that the locally produced bacterial phytase obtained from Enterobacter sakazakii273 could be as effective as the commercially produced fungal phytase (Natuphos®). Further researches are recommended to determine the optimum level of available P in order to produce maximum performances (body weight gain, feed intake, feed conversion ratio, bone mineralization, mineral retention, and P excretion in the environment) using larger number of chickens. The cellmediated immunity in broilers vaccinated against ND and IBD vaccines should also be measured to assess the real effect on immune response by local phytase supplementation in low P diet. In addition, phytase from ASUIA273 can be used to a diet to determine the impacts on vitamin-D,parathormone, glucocorticoids, and thyroids in animal body.